2014
DOI: 10.1016/j.jvn.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The lived experiences of patients post coronary angioplasty: A qualitative study

Abstract: Few qualitative studies have focused on the experiences of patients post angioplasty. A deep understanding of patient experiences of care and the way a treatment can affect their everyday life is particularly important in chronic disease management. The aim of this study was to explore experiences that patients undergo after angioplasty. Using a phenomenological study design, 15 patients participated in individual, face-to-face, semistructured interviews. Data were analyzed using qualitative content analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This is not only isolated to Australia, with some countries in Europe having similar short lengths of hospital stay (Wilkins et al, 2017). While there is recent international evidence about the experiences of cardiac patients (Esmaeili, Cheraghi, & Salsali, 2016;Fors, Dudas, & Ekman, 2014;Hasankhani et al, 2014), their educational experiences are largely unknown. The only qualitative study to specifically explore the information needs of cardiac patients was conducted over a decade ago (Hanssen, Nordrehaug, & Hanestad, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This is not only isolated to Australia, with some countries in Europe having similar short lengths of hospital stay (Wilkins et al, 2017). While there is recent international evidence about the experiences of cardiac patients (Esmaeili, Cheraghi, & Salsali, 2016;Fors, Dudas, & Ekman, 2014;Hasankhani et al, 2014), their educational experiences are largely unknown. The only qualitative study to specifically explore the information needs of cardiac patients was conducted over a decade ago (Hanssen, Nordrehaug, & Hanestad, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Providing patients with specific information about the short‐term benefits of coronary stent implantation as well as the lifestyle changes that it may require should be able to reduce their anxiety 50,51 . Patient involvement is increasingly being recognized as a fundamental aspect of the proper management of chronic diseases, especially those affecting the heart 52,53 . The provision of clear and detailed information about coronary stent implantation could have influenced the participants' early lived experiences 54 .…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Patient involvement is increasingly being recognized as a fundamental aspect of the proper management of chronic diseases, especially those affecting the heart. 52,53 The provision of clear and detailed information about coronary stent implantation could have influenced the participants' early lived experiences. 54 However, in other studies, [55][56][57][58] the authors have identified strategies to reduce anxiety, especially in emergency cases.…”
Section: Lifestyle Changes After Surgerymentioning
confidence: 99%
“…Patients' experiences play a significant role in the successful outcomes of angioplasty (8). In addition to raising physical problems, diagnosis of acute MI leads to a significant disorder in the patients' psychological condition including anxiety, depression, and uncertainty about the future.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, patients may require reangioplasty after several years. The previous experiences may affect their degree of reacceptance of angioplasty (8).…”
Section: Introductionmentioning
confidence: 99%